Analysis of the economic and commercial impacts suffered by family farmers during the COVID-19 pandemic - Lopes , Rafaela Dembiski; Murata , Marília Pinto Ferreira; Murata , Afonso Takao (Seven Editora, 2023)
The article in question addresses the economic and commercial impacts suffered by family farmers during the Covid-19 pandemic. This is a field study, exploratory and descriptive in nature and quantitative and qualitative in approach. The research includes individuals over 18 years old who self-declare as family farmers and reside in any area of the Brazilian territory. Data collection addressed issues related to the production and marketing of products, the economic situation of individuals, difficulties, limitations, changes, and adaptations covering the period of the pandemic. During this research period, the three main activities performed by family farmers were: vegetable production (72.3%), grain production (36.9%), and fruit growing (30.8%). The family farmers interviewed used more than one way to market their products, the two main ones being: selling in open fairs (performed by 55.4%) and selling directly to consumers or establishments (32.3%), besides using public policies such as PNAE (29.2%) and PAA (26.2). However, during the pandemic, many faced difficulties, such as reduced demand due to the closure of consumer establishments and lack of access to emergency aid. In addition, 76.9% of the farmers admitted to having their marketing affected and 60% had a reduction in their income. Despite this, new alternatives were developed to face these challenges, among them the extensionist actions that were fundamental in the creation of a new form of commercialization (virtual fair). These results highlight the need for specific policies and support measures for family farmers during crises such as the Covid-19 pandemic. DOI:https://doi.org/10.56238/emerrelcovid19-047